Reflective Case Discussion (RCD) for Nurses : A Systematic Review - Amir, Haeril; Sudarman, Sudarman (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The aim of this study was to determine the benefits of RCD on nurses themselves, this literature through identification from the Pubmed database, Science direct and online wiley, use the keywords ’Reflection’ and ’Case’ and ’Nursing’. The method of searching articles uses PICOT technique, Prism Flow diagram, abstraction and synthetic data. Through fulltext screening, double publication and eligibility, 455 research articles were found. The next step is to screen through the inclusion criteria and exclusion criteria so that the final result of the article found is 4 articles. Articles have a lot to explain about the benefits RCD for nurses, RCD can add to the knowledge of nurses, minimize the gap theory and practice so that errors can be resolved. Literature is also finding benefits RCD on nurses is increasing the professionalism of the work and cooperation among fellow colleagues. Implementation of the RCD environment of clinical very ber benefits